Teaching Reading Comprehension Through Genre-Based Approach (GBA) at Senior High School - Gunawan Gunawan (Acitya: Journal of Teaching and Education, 2022)
This research is about teaching reading comprehension through a genre-based approach (GBA) at senior high school. The study aimed to increase students' reading comprehension in the eighth grade at SMP Negeri 1 Sibulue through the Genre-Based Approach (GBA). This research used Classroom Action Research (CAR) that consisted of two cycles. The research subject was the eighth grade of SMP Negeri 1 Sibulue academic year 2021/2022 that consisting of 25 students. The researcher obtained the data by using a reading test and observation sheet. The results of the students’ reading tests in cycle I and cycle II had significantly different scores. There was a better increase of gains by students at the end of the action of the second cycle. The results of the study showed that the score in the first cycle to the second cycle increased based on the value of the first cycle of 61.80 and the second cycle showed 75.80. It could be stated that the student's reading comprehension at the eighth grade of SMP Negeri 1 Sibulue was at a fairly good level after the test in the first cycle and increased to a good level after the test in the second cycle.